Unveiling Segregation’s Impact: Analyzing the Relationship Between Dimensions and Police-Involved Homicide of Minorities in U.S. Counties - Zhao, Yunhan (Crime & delinquency, 2025)
Literature on police-involved homicide has failed to explore the influences of differential segregation dimensions. Analyzing data from 584 U.S. counties, we assessed the effects of five segregation dimensions for Blacks and Hispanics. Black police-involved homicide risk was lower in counties with increased evenness and exposure segregation dimensions, but higher in areas with elevated clustering. However, the risk for Hispanics was higher in counties with greater centralization and concentration, yet lower in areas with reduced clustering. Moreover, the association between the outcome and specific segregation indicators was moderated by the minority population share. Different segregation dimensions impact police-involved homicide for minorities through distinct mechanisms. Policies reducing police killings should be tailored by social group and area characteristics.